RELATIONSHIP OF ORGANIC MATERIAL WITH ABUNDANCE OF TOXIC BENTHIC DINOFLAGELLATA ON SEDIMENT IN WATERS OF TELUK BAKAU VILLAGE BINTAN REGENCY, RIAU ISLAND PROVINCE - Afrizani, Syafrinaldi; Nurrachmi, Irvina; Effendi, Irwan (Asian Journal of Aquatic Sciences, 2019)
Dinoflagellata was included in one of microalgae groups which are on waters of the sea and the river, it can be found on detritus floats, sediments, and also swim freely. This research done on May – June 2018 at waters of the mangrove bay village, Bintan Regency, Riau Island Province. The aims of this research was to know relationship between organic material concentration toward abundance of toxic benthic dinoflagellata on sediment. In addition, to analyzed organic material concentratin and amount of abundance of toxic benthic dinoflagellata on sediment in waters of Teluk Bakau. The method used was survey method which is the location of sampling is done by pursosive sampling. Measurement of water quality sampling done at any point, the surface water temperature range 31-33oC, 28-31 ‰ salinity, pH 8-9 and the current speed from 0.045 to 0.051 m / det.Perairan predominantly sandy gravel sediments, making an average of organic materials ditemukn at each station is 0.027%, 0.043%, 0.033%, 0.024%. The result of this research found 3 genus of toxic dinoflagellata, which are Prorocentrum, Gambierdiscus, and Ostreopsis. Poisonous dinoflagelatta can produced a several types of toxic that found the sea. The highest of abundance found at station 2 on 75,615 sel/m2 and the lowest found at station 1 on 35,176 sel/m2. the results of simple linear regression analysis the relationship between the concentration of organic material with the abundance of dinoflagellates has a positive relationship with the regression equation y = 32,913 + 556,13x